Uranyl tris-(carbohydrazide) nitrate [UO2((N2H3)2CO)3](NO3)2: synthesis, structure and properties; Radiochimica Acta; Vol. 103, iss. 7 - Leshok D. Y. Darya Y.; Alekseenko V. N. Vladimir N.; Gavrilov P. M. Peter Mikhailovich; Alekseenko S. N. Sergei N.; Dyachenko A, S. Anton S.; Samoilo A. A. Alexander A.; Kondrasenko A. A. Alexander A.; Kirik S. D. Sergei D. (2015, 2015)
Title screen